Learning Abilities of Students with Intellectual Disabilities for Cooking Indonesian Traditional Food â€œOpak Bakarâ€: From Step by Step Experiment to the Analysis - Vina Pemila Apriyanti (Indonesian Journal of Community and Special Needs Education, 2023)
Children with intellectual disabilities are children who experience delays in the development of intelligence, they experience various kinds of obstacles. Therefore, children with intellectual disabilities are less able to be developed their academic learning and require development in other learning, namely in learning skills, one of which is learning the skills of making Indonesian traditional food "Opak Bakar". The skill of making â€œOpak Bakarâ€ is taught in schools. This study aims to determine the ability to make Indonesian traditional food â€œOpak Bakarâ€ skills in class X children with intellectual disabilities. Following the objectives to be achieved, this study used a descriptive method with a qualitative approach, data obtained through observation, interviews, and documentation studies. This research was conducted on 3 children with intellectual disabilities and 1 class X skills teacher. One of the theories that underlie this research is the task analysis theory. The results showed that mild children with intellectual disabilities were able to make grilled â€œOpak Bakarâ€, which started by washing rice, making glutinous rice, adding rice flour, drying opak, and burning â€œOpak Bakarâ€. Some children find it difficult to mix the glutinous rice, print the glutinous rice into a rectangle, cut the â€œOpak Bakarâ€ thin and rectangular shape and determine the color of the Indonesian traditional food â€œOpak Bakarâ€. This study recommends that schools complete skills teaching aids that are following the types of skills programs in schools.